2009
DOI: 10.1002/btpr.104
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of endo‐β‐1,4‐mannanase from Aspergillus fumigatus in Aspergillus sojae and Pichia pastoris

Abstract: in Wiley InterScience (www.interscience.wiley.com).To be utilized in biomass conversion, including ethanol production and galactosylated oligosaccharide synthesis, namely prebiotics, the gene of extracellular endo-b-1,4-mannanase (EC 3.2.1.78) of Aspergillus fumigatus IMI 385708 (formerly known as Thermomyces lanuginosus IMI 158749) was expressed first in Aspergillus sojae and then in Pichia pastoris under the control of the glyceraldehyde triphosphate dehydrogenase (gpdA) and the alcohol oxidase (AOX1) promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 23 publications
0
25
0
2
Order By: Relevance
“…The specific activity of rMan5P1 was 1703.1 ± 101.2 U/mg, which is lower than that of MAN5A from Bispora sp. MEY-1 (3373 U/mg; Luo et al, 2009), and b-mannosidase from A. niger BK01 (2570 U/mg; Do et al, 2009), but significantly higher than that of Man5XZ7 from T. arenaria XZ7 (704.5 U/mg; Lu et al, 2013), MANN from A. sulphureus (366 U/mg;Chen et al, 2007), PpMan from A. fumigatus (350 U/mg; Duruksu et al, 2009), and Man5XZ3 from A. nidulans XZ3 (184.8 U/mg; Lu et al, 2014).…”
Section: Substrate Specificity and Kinetic Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…The specific activity of rMan5P1 was 1703.1 ± 101.2 U/mg, which is lower than that of MAN5A from Bispora sp. MEY-1 (3373 U/mg; Luo et al, 2009), and b-mannosidase from A. niger BK01 (2570 U/mg; Do et al, 2009), but significantly higher than that of Man5XZ7 from T. arenaria XZ7 (704.5 U/mg; Lu et al, 2013), MANN from A. sulphureus (366 U/mg;Chen et al, 2007), PpMan from A. fumigatus (350 U/mg; Duruksu et al, 2009), and Man5XZ3 from A. nidulans XZ3 (184.8 U/mg; Lu et al, 2014).…”
Section: Substrate Specificity and Kinetic Parametersmentioning
confidence: 96%
“…Until now, the thermophilic fungi Talaromyces leycettanus JCM12802 (Wang et al, 2014a), Aspergillus fumigatus IMI 385708 (Duruksu, Ozturk, Biely, Bakir, & Ogel, 2009), Aspergillus nidulans XZ3 (Lu et al, 2014), Humicola insolens Y1 (Luo et al, 2012), Thielavia arenaria XZ7 (Lu et al, 2013), and Rhizomucor miehei (Katrolia et al, 2013) have been reported be the ideal microbial sources of excellent b-mannanases.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, recombinant Aspergillus sojae transformant 1 (AsT1) (DURUKSU et al, 2009) was used, which was obtained from Prof. Dr. Z.B. Ogel's laboratory (Middle East Technical University, Ankara, Turkey).…”
Section: Methodsmentioning
confidence: 99%
“…The stock culture was grown on potato dextrose agar (PDA) at 30 ºC for 4-5 days, stored at 4 ºC, and sub-cultured bi-monthly. Inoculum was prepared by washing each incubated PDA agar plate with 5 ml of sterile saline (0.8%, w/v) and Tween-80 (0.005%, v/v) mixed solution (DURUKSU et al, 2009;OZTURK et al, 2010). The resulting suspension solution had about 4.0×10 7 spores per ml.…”
Section: Methodsmentioning
confidence: 99%
“…For example, recombinant β-mannanases of Aspergillus sulphureus [14], Bispora sp. MEY-1 [15], and Aspergillus fumigatus [16] have been produced in Pichia pastoris and showed activity up to 500 U ml −1 . However, due to the limitations of knowledge for enzyme function, application of fungal mannanases is still confined.…”
Section: Introductionmentioning
confidence: 99%